Pengaruh Pemahaman Peraturan Perpajakan Terhadap Kepatuhan WPOP Dengan Preferensi Resiko Sebagai Variabel Pemoderasi - Ayu Utari, Putu Devi; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
Badung Utara, Badung Utara, Badung Utara. To find out whether the preference must be able to moderate the relationship between understanding of tax regulations on individual taxpayer regulations in the North Badung region. The minimum number of samples used in the study were 100 (one hundred) individual taxpayers at North Badung KPP Pratama. This study uses the accidential sampling method. The method of data collection uses the questionnaire method. The data analysis technique used is Moderated Regression Analysis (MRA). The results obtained related to understanding tax regulations, positive and significant to taxpayer obligations, as well as risk preferences can moderate the relationship of understanding tax regulations with taxpayer assistance. Keywords: Understanding of Taxes, Tax Compliance, Risk Preference.